2020
DOI: 10.1111/apt.15706
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of either ustekinumab or vedolizumab in 239 patients with Crohn's disease refractory to anti‐tumour necrosis factor

Abstract: Background:There is no head-to-head trial comparing ustekinumab and vedolizumab in patients with Crohn's disease (CD) refractory to anti-tumour necrosis factor (anti-TNF). Aim:To compare the effectiveness and safety of ustekinumab and vedolizumab in patients with CD refractory to anti-TNF in a multicentre retrospective observational cohort.Methods: All consecutive patients with CD refractory or intolerant to anti-TNF who initiated either vedolizumab or ustekinumab were included between May 2014 and August 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
120
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(140 citation statements)
references
References 43 publications
15
120
4
1
Order By: Relevance
“…Comparison between the two treatment groups is limited by the small number of patients. It is unlikely, however, that our findings are reflective of sample size limitations as our findings are consistent with that reported previously 15,26 . Our centre does not mandate endoscopic follow‐up and therefore we do not have data on mucosal healing.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Comparison between the two treatment groups is limited by the small number of patients. It is unlikely, however, that our findings are reflective of sample size limitations as our findings are consistent with that reported previously 15,26 . Our centre does not mandate endoscopic follow‐up and therefore we do not have data on mucosal healing.…”
Section: Discussionsupporting
confidence: 64%
“…It is possible but unlikely that our universal policy of treating patients with 8‐weekly and not 12‐weekly ustekinumab in anti‐TNF refractory Crohn's disease may have accounted for some of the efficacy differences. However, it is noteworthy that other real‐world cohorts which utilised a 8‐ or 12‐weekly ustekinumab dosing schedule also showed superior effectiveness of ustekinumab compared to vedolizumab 6,26 . Moreover, dose titration to 4‐weekly vedolizumab was also allowed within our study.…”
Section: Discussionmentioning
confidence: 83%
“…DvL has received educational grants or research support from Pfizer, Takeda, Ferring, Shire and has received consultancy and/or speaker's fees from Pfizer, Janssen, AbbVie, Ferring, Vifor and Emerge Health. Ashish Srinivasan 1,2,3 Peter De Cruz 1,4 Daniel R. van Langenberg 1,3…”
Section: Ack N Owled G Em Entmentioning
confidence: 99%
“…There is ongoing controversy about whether ustekinumab is superior to vedolizumab in patients with Crohn's disease (CD) refractory to anti‐tumour necrosis factor (anti‐TNF) agents 1‐3 . Among these, the prospective head‐to‐head comparison study 1 performed by Biemans et al indicated that ustekinumab is associated with superior outcomes compared to vedolizumab.…”
mentioning
confidence: 99%